Development of a weigh-band for pigs in Uganda (Data on weights and body measurements of Ugandan pigs) - Marshall, Karen; Poole, Elizabeth J.; Ouma, Emily A.; Kugonza, Donald R. (International Livestock Research Institute, 2022)
Knowledge of the body weight in pigs is important in informing management decisions and, often, negotiating a sale price. In the smallholder pig system in Uganda the smallholder pig keepers usually do not know the body weights of their animals nor have access to scales. To overcome this, we propose to collect body measurement of pigs with the following objectives: 1. Determine the best predictive equation for weight from body measurement for (a) all animals, and (b) subsets of animals (e.g., grouped by weight, age, sex) 2. Estimate the loss in predictive accuracy in only using one variable for all animals and subsets of animals (testing this as one predictive variable makes a weigh-band a viable option) 3. Should one variable not be viable explore the options for making a farming friendly tool for predicting weight (weigh band, table, app etc.) 4. Synthesis and reporting of results including sharing with local partners 5. Production and dissemination of weight bands (or alternative tool) to participating farmers. Exploration of options for a distributor of these (e.g.private sector partner) The dataset is provided along with the ODK tool used to collect the data (the dictionary for coded variables can be found on the Choices sheet)